Overlay Spectrum Reuse in a Multicarrier Broadcast Network: Single Receiver Analysis - Alberto Rico-Alvariño; C. Mosquera; Fernando Pérez-González (The 13th IEEE International Workshop on Signal Processing Advances in Wireless Communications (SPAWC 2012), 2012)
The overlay cognitive radio paradigm presents a framework where a secondary user exploits the knowledge of the primary user's message to improve spectrum utilization. A multicarrier broadcast network is one of the scenarios where this knowledge is possible: the secondary user could join a single frequency network and, therefore, gain access to the primary message. However, if the primary signal is received with a strong line of sight component, its relaying from the secondary transmitter does not suffice to ensure the primary user quality of service. In this paper we study the scenario where a secondary transmitter maximizes its own transmission rate, keeping the quality of a primary receiver over a given threshold. The analytical results, based on bit error rate bounds, are verified by means of software simulations and hardware tests.
Keywords: cognitive radio; dynacs